Extracellular matrix degradation via enolase/plasminogen interaction: Evidence for a mechanism conserved in Metazoa. (25th February 2016) - Grossi, Gerarda; Grimaldi, Annalisa; Cardone, Rosa A.; Monné, Magnus; Reshkin, Stephan J.; Girardello, Rossana; Greco, Maria R.; Coviello, Elena; Laurino, Simona; Falabella, Patrizia
Research article: Insect parasitoids perform an astonishing number of strategies to regulate host physiology in favour of their progeny development. Maternal and, sometimes, embryonic factors release molecules involved in nutritional suitability of hosts. While host tissue invasion and digestion is not a novelty in parasitism, here we demonstrate in insects the use of a mechanism conserved in several other organisms, where invasive capacity is based on the recruitment and activation of plasminogen/plasminogen‐like proteins. Furthermore, our data also confirm that Ae ‐ENO is a novel example of multifunctional protein in insects. Abstract : Background Information: While enolase is a ubiquitous metalloenzyme involved in the glycolytic pathway, it is also known as a multifunctional protein, since enolases anchored on the outer surface of the plasma membrane are involved in tissue invasion. Results: We have identified an extracellular enolase ( Ae ‐ENO) produced by the teratocytes, embryonic cells of the insect parasitoid Aphidius ervi . We demonstrate that Ae ‐ENO, although lacking a signal peptide, accumulates in cytoplasmic vesicles oriented towards the cell membrane. Ae ‐ENO binds to and activates a plasminogen‐like molecule inducing digestion of the host tissue and thereby ensuring successful parasitism. Conclusions: These results support the hypothesis that plasminogen‐like proteins exist in invertebrates. Interestingly the activation of a plasminogen‐like protein is mediated by a mechanisms involving the surface enolase/fibrinolytic system considered, until now, exclusive of vertebrates, and that instead is conserved across species. Significance: To our knowledge, this is the first example of enolase mediated Plg‐like binding and activation in insect cells, demonstrating the existence of an ECM degradation process via a Plg‐like protein in invertebrates.